The imagined Canadian: Representations of whiteness in "Flashback Canada". - Montgomery, Kenneth Edward. (University of Ottawa (Canada), 1999)
This anti-racist study is one which critically investigates the representation of whiteness in a Canadian history textbook approved for use in Ontario's intermediate division schools. Fundamental to the study is the identification of racializations and the manner by which these representational processes work with and through concepts of nationality and ethnicity to separate whiteness from otherness. To facilitate this critical analysis, the historical narratives of the textbook are examined for redundant portrayals of individuals and groups in terms of their power, problem-resolution, and performance. In addition, the stories of Canada's past are analyzed to determine the extent to which diverse perspectives are included and the degree of significance attached to historic and contemporary racisms. The findings suggest that, in Flashback Canada, processes of racialization articulate with signifiers of ethnicity and nationality to imagine Canada and Canadians along white supremacist lines.
Keywords: Canadian Studies.